Avaliação da via aérea superior em pacientes classe III submetidos à cirurgia ortognática: revisão de literatura - Silva, Lucas Martins Castro e; Pereira Filho, Valfrido Antonio [UNESP]; Moraes, Márcio de; Melleiro Gimenez, Carla Maria [UNESP] (My University, 2014)
Introduction: The configuration and dimensions of the upper airway are determined by anatomical structures such as soft tissues, muscles and craniofacial skeleton, composing or surrounding the pharynx. Anatomical abnormalities of the soft tissues and / or craniofacial skeleton may become more narrow upper airway. The orthognathic surgery, which is used in the correction of dentoskeletal deformities, also causes changes in the upper airway. Objective: In view of the facts presented, this article aims to review the literature on the changes of the upper airway in patients’ class III undergoing orthognathic surgery. Methodology: International Literature on Health Sciences (Pubmed ) and Port Journals CAPES original and review published between 1990 and 2010, in two bibliographic databases articles were selected. Results: thirty-nine (39) articles were selected for writing this review. Conclusion: The upper airway deformity and dental- skeletal class III should be carefully evaluated prior to orthognathic surgery and whenever surgical planning permit should prefer the maxillary advances to mandibular setbacks

Introdução: A configuração e as dimensões da via aérea superior são determinadas pelas estruturas anatômicas como: tecidos moles, musculatura e esqueleto craniofacial, que compõem ou circundam a faringe. As alterações anatômicas dos tecidos moles e/ou do esqueleto craniofacial poderão tornar a via aérea superior (VAS) mais estreita. A cirurgia ortognática, que é utilizada na correção das deformidades dento-esqueléticas, leva também a alterações na VAS. Objetivo: Em vista dos fatos apresentados, o presente artigo tem como objetivo realizar uma revisão da literatura sobre as alterações da via aérea superior em pacientes classe III submetidos à cirurgia ortognática. Metodologia: Foram selecionados artigos originais e de revisão publicados entre 1990 e 2010, em duas bases de dados bibliográficos –Literatura Internacional em Ciências da Saúde (Pubmed) e Porta de Periódicos CAPES. Resultados: Foram selecionados trinta e nove (39) artigos para a escrita dessa revisão. Conclusão: A via aérea superior e a deformidade dento-esquelética classe III devem ser avaliadas cuidadosamente antes da cirurgia ortognática e sempre que o planejamento cirúrgico permitir deve-se preferir os avanços maxilares aos recuos mandibulares.
Assesment of upper airway in class III patients undergoing orthognathic surgery: literature review
Keywords: Prognathism; Apnea; Mandible; Malocclusion; Prognatismo; Apneia; Mandíbula; Má oclusão